An integrated migration and transformation model to evaluate the occurrence characteristics and environmental risks of Nitrogen and phosphorus in constructed wetland. (August 2021) - Li, Hongrui; Ma, Xiaodong; Zhou, Bin; Ren, Gengbo; Yuan, Dekui; Liu, Honglei; Wei, Zizhang; Gu, Xiujun; Zhao, Bin; Hu, Yanhua; Wang, Hongguang
Abstract: In this study, an integrated migration and transformation (IMT) model based on microbial action, plant absorption, sediment release and substrate adsorption was firstly established to evaluate the temporal-spatial distribution of N and P in Lingang hybrid constructed wetland (CW), Tianjin. Compared to the conventional transformation model that only considers the microbial action, the IMT model could accurately predict the occurrence characteristics of N and P. In Lingang CW, NO3 − -N (0.56–3.63 mg/L) was the most important form of N, and the TP was at a relatively low concentration level (0.04–0.07 mg/L). The spatial distribution results showed that a certain amount of N and P could be removed by CW. Form the temporal perspective, the N and P concentrations were greatly affected by the dissolved oxygen (DO). The simulated values obtained by IMT model indicated that the distribution of N and P was more affected by the temporality compared with the spatiality, which was consistent with measured values. Besides, the PCA indicated that TN, NO3 − -N and DO were important factors, which affected the water quality of CW. The Nemerow pollution index method based on the simulated values indicated that Lingang CW was overall moderately polluted, and the subsurface area was the main functional unit of pollutants removal in CW. This work provides a new model for accurately predicting the occurrence characteristics of N and P pollutants in CW, which is of great significance for identifying its environmental risks and optimizing the construction of wetlands. Graphical abstract: Image 1 Highlights: An IMT model based on microbial action and source terms was firstly established. IMT model can accurately predict the distribution and environmental risk of N, P. Distribution and PCA indicated that CW pollution was related to TN, NO3 − -N and DO. The subsurface wetland was the main functional unit of pollutants removal.